Joint impact of serum urate, renal function, and genetic susceptibility on coronary heart disease and ischemic stroke risk: a population-based study - Guo, Huangda; Wang, Siyue; Peng, Hexiang; Hou, Tianjiao; Li, Yixin; Zhang, Hanyu; Wang, Mengying; Wu, Tao; Huang, Jie (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between serum urate and cardiovascular disease (CVD) is well-established, but its interplay with renal function and genetic susceptibility remains less clear. The study aimed to investigate the individual and joint associations of serum urate, renal function, and genetic risk with incident CVD.MethodsThe study included 383,390 participants from the UK Biobank, initially free of CVDs at baseline. Serum urate levels and kidney damage markers were obtained. We used a new approach to construct an estimated glomerular filtration rate, and incorporate albumin-creatinine ratio to assess renal function. Genetic risk scores for CHD and IS were calculated. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox models.ResultsOver a median 13.24-year follow-up, 35,932 CVD events were documented, including 30,025 CHD and 5,524 IS cases. Each standard deviation increase in urate was associated with HRs (95% CIs) of 1.09 (1.08, 1.11) for CVD, 1.08 (1.08, 1.11) for CHD, and 1.12 (1.08, 1.15) for IS. Elevated urate, in combination with impaired renal function or higher genetic risk, further increased CVDs risk. Participants with poor renal function and the highest tertile urate had approximately three times the risk of CVDs compared to those with normal kidney function and the lowest urate tertile. Similar trends were observed for the joint impact of genetic susceptibility and urate.ConclusionsOur findings underscore the importance of managing urate levels in individuals with renal impairment or genetic susceptibility in the prevention of CVDs.